The stress-strength model and its generalizations : theory and applications - Kotz, Samuel (World Scientific, 2003)
This important book presents developments in a remarkable field of inquiry in statistical/probability theory - the stress-strength model. Many papers in the field include the enigmatic "words" P(X<Y) - or something similar - in the title. This reflects the long-established concept of ordering of distributions. The basic impetus for the study carried out by the authors of this book is the general concept of stress-strength as an interpretation of the P(X<Y) relationships, which leads to applications in reliability engineering, economics and modern medicine. The Stress-Strength Model and Its Generalizations collects and digests theoretical and practical results on the theory and applications of the stress-strength relationships in industrial and economic systems - results that have been scattered in the literature during the last 40-odd years - and augments and presents them for the first time in a unified manner suitable for practitioners as well as probabilists and theoretical and applied statisticians.